Comparative assessment of sugar and malic acid composition in cultivated and wild apples. (1st April 2015) - Ma, Baiquan; Chen, Jie; Zheng, Hongyu; Fang, Ting; Ogutu, Collins; Li, Shaohua; Han, Yuepeng; Wu, Benhong
Highlights: In this study, soluble sugar and malic acid contents in mature fruits of 364 apple accessions, including 321 cultivars worldwide and 43 wild relatives, were quantified using high-performance liquid chromatograph. Overall, wild apples showed greater variations in sugar and malic acid contents than cultivated apples. This indicates wild Malus species are useful sources of genetic variation for apple breeding. Interestingly, our study indicates a signature of a domestication syndrome: reduced fruit acidity that is typically associated with domestication. Abstract: Soluble sugar and malic acid contents in mature fruits of 364 apple accessions were quantified using high-performance liquid chromatography (HPLC). Fructose and sucrose represented the major components of soluble sugars in cultivated fruits, whilst fructose and glucose were the major items of sugars in wild fruits. Wild fruits were significantly more acidic than cultivated fruits, whilst the average concentration of total sugars and sweetness index were quite similar between cultivated and wild fruits. Thus, our study suggests that fruit acidity rather than sweetness is likely to have undergone selection during apple domestication. Additionally, malic acid content was positively correlated with glucose content and negatively correlated with sucrose content. This suggests that selection of fruit acidity must have an effect on the proportion of sugar components in apple fruits. Our study provides information that could be helpful for future apple breeding.